ANALISIS PENCATATAN AKUNTANSI MUDHARABAH DEPOSITO BATARA IB MENURUT PSAK NO. 105 PADA PT. BANK TABUNGAN NEGARA SYARIAH CABANG PEKANBARU - Wan Junita Raflah; Wan Zulhaq Akmarullah (Politeknik Negeri Bengkalis, 2018)
PT. Bank Tabungan Negara Syariah Pekanbaru Branch is one of the institutions operating in sharia principles. In practice, PT. Bank Tabungan Negara Syariah Pekanbaru Branch distributes various products to the community with various contracts (Aqad)in accordance with what is needed by its customers. One of the funding products offered is mudharabah deposits accaount using aqad mudharabah. This research was conducted at PT. Bank Tabungan Negara Syariah Pekanbaru Branch which is located at Jl. Tuanku Tambusai Block A. No. 10-11 Labuh Baru Timur Payung Sekaki. The purpose of this study is to find out about the application of accounting conducted by this bank, the authors want to know whether it has been implemented in accordance with the PSAK No. 105 standard. In this study, the author uses descriptive method in which the authors obtain data from interviews and documentation directly from the bank. The results showed that the application of mudharabah deposit accounting at PT. Bank Tabungan Negara Syariah Pekanbaru Branch using Cash Basis method is a method of comparison between income and expenses where income is reported when the money has been received and expenses are reported when the money has been paid. While profit sharing to customers using Revenue Sharing principle where rates (Nisbah) for deposit accaount products is greater for customers than for the banks. With a ratio of 44% for customers as owners of funds and 56% for the bank as a fund manager.